HUBUNGAN EKSPRESI miRNA-21 DENGAN TARGET PDCD4 DAN miRNA-143 DENGAN TARGET BLC-2 PADA KASUS KANKER SERVIKS - Nikki Aldi Massardi; Soemanadi; Beti Ernawati Dewi; Dewi Wulandari; Eduardus Gilang Putra (Bioma, 2023)
A study has been carried out to compare the expression of miRNA-21 and miRNA-143 with target mRNA PDCD4 and BCL-2 in cases of early-stage cervical cancer compared to advanced stages. These data can be used as information for the development of non-invasive cervical cancer prognostic methods. The study was conducted by taking serum samples and exfoliativecell samples from normal subjects and subjects with cervical cancer detection and then analyzed using qRT-PCR. Samples of cervical cancer patients consisting of 15 subjects and 4 normal subjects were used to obtain relative quantity values for the expression of miRNA-21, miRNA-143, mRNA PDCD4 and BCL-2. In the study of miRNA-21, there was no significant difference in determining cervical cancer with p>0.05 using the t-test (0.594) and a significant relationship was found between miRNA 21 and PDCD4 with a strong correlation (p<0.05, r = -0.563; Pearson). The relationship between miRNA-143 and the Bcl-2 target gene in this study showed a weak and insignificant correlation (r = -0.101; p > 0.05; Pearson). There was a significant relationship between miRNA-21 and PDCD4 in early-stage and advanced-stage samples, while the relationship between miRNA-143 and the Bcl-2 mRNA target gene showed no significant correlation.